2008
DOI: 10.1080/14756360701546595
|View full text |Cite
|
Sign up to set email alerts
|

Modulation ofAnopheles gambiaeEpsilon glutathione transferase activity by plant natural productsin vitro

Abstract: Elevated glutathione transferase (GST) E2 activity is associated with DDT resistance in the mosquito Anopheles gambiae. The search for chemomodulators that inhibit the function of AgGSTE2 would enhance the insecticidal activity of DDT. Therefore, we examined the interaction of novel natural plant products with heterologously expressed An. gambiae GSTE 2 in vitro. Five of the ten compounds, epiphyllocoumarin (Tral-1), knipholone anthrone, isofuranonaphthoquinones (Mr 13/2, Mr13/4) and the polyprenylated benzoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…The specific activity of AgGST ε 2 is also comparable with the activities described for other recombinant AgGST ε 2 of the same class, for example, the specific activity of AgGST ε 1 with CDNB as a substrate was reported to be 56.4  μ mol min −1  mg −1 [19]. The molecular weight of AgGST ε 2 obtained was 25 kDa (Figure 2), a value which is the same as the literature value [26]. …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The specific activity of AgGST ε 2 is also comparable with the activities described for other recombinant AgGST ε 2 of the same class, for example, the specific activity of AgGST ε 1 with CDNB as a substrate was reported to be 56.4  μ mol min −1  mg −1 [19]. The molecular weight of AgGST ε 2 obtained was 25 kDa (Figure 2), a value which is the same as the literature value [26]. …”
Section: Resultssupporting
confidence: 82%
“…Epoxy activated Sepharose 6B (Pharmacia Biotech, Uppsala, Sweden) affinity gel was used for affinity chromatography purification of AgGST ε 2 as described before [26]. In order to determine the tubes in which most of the enzyme was located, a 1-chloro-2,4-dinitrobenzene (CDNB) assay was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that GSTs are able to interact covalently and noncovalently with various compounds that are not substrates for enzymatic activity [28]. GST activity has been shown to be modulated by natural plant products [29,30]. Flavonoids have been shown to inhibit GSTs in human blood platelets as well as in cancer cell lines [31].…”
Section: Discussionmentioning
confidence: 99%